On materials use training in efl teacher education: some reflections (2006)
This paper reports on the findings of a case study carried out at Universidad de Antioquia as well as explores training on materials use in our teacher preparation program and its effectiveness in the practicum. The data analyzed suggest that, although teacher educators having new approaches to train future teachers in materials use, they still need to revise the way they include this component in teacher preparation curricula. Training in the use of materials should include their use in settings with limited resources as well as those with greater possibilities in technical and non-technical materials. Lastly, the author raises awareness about the need to include materials use as an issue in local and national EFL teacher education agendas. Key words: Materials use, training, teacher education, practicum Este artículo presenta los resultados de un estudio de caso llevado a cabo en la Universidad de Antioquia en el que se exploró la capacitación que damos a nuestros estudiantes de pregrado en el uso de materiales y su efectividad en la Práctica Docente. El análisis de los datos sugiere que a pesar del avance en la forma como los formadores de docentes tratamos el uso de los materiales, se hace necesaria una revisión de la forma cómo los estudiantes son expuestos a este uso. La formación en el uso de los materiales debe incluir contextos escolares en los que haya recursos limitados y aquellos donde haya mayores posibilidades en materiales técnicos y no técnicos. Finalmente, la autora llama la atención sobre la necesidad de incluir el uso de los materiales como un punto en las agendas de formación de docentes a nivel local y nacional. Palabras claves: Uso de materiales, entrenamiento, formación docente, práctica docente